Is There a Doctor in the House? Expert Product Users, Organizational Roles, and Innovation - Katila, Riitta; Thatchenkery, Sruthi; Christensen, Michael Q.; Zenios, Stefanos (Academy of Management Journal, 2017)
We explore the impact on innovation that domain experts, i.e., professional end users of a product have as inventors, executives, and board members in a young organization. Using a dataset of 231 surgical instrument ventures spanning a 25-year period alongside in-depth qualitative fieldwork, we find that professional physician–users (surgeons) strengthen innovation in some roles but block it in others. These experts are related to an increase in a firm’s innovation when they take a technology role as inventors, and particularly when they take a governance role on a fledgling firm’s board. However, despite their frequent involvement in executive roles, surgeon–executives are less likely to be helpful, and especially likely to block innovation, as chief executives. Our results emphasize expert users as a critical external dependency for a young firm’s innovation, but show that expertise can backfire when there is a mismatch with a particular organizational role. A key finding is that expert users are more helpful in suggesting a broad variety of solutions to a firm’s innovation problems but less helpful in selecting the best ones for the organization to pursue. Our findings have implications for research on the evolutionary perspective of innovation, user experts and their organizational roles in young firms, and entrepreneurial policy.